Factors associated with tetanus, diphtheria and pertussis (Tdap) vaccination acceptance among pregnant women: a cross-sectional study - Aziz, Nurhasifah Abd; Zulkefli, Nor Afiah Mohd; Abdullah, Zainab Hananah Abang (BioMed Central Ltd, 2026)
Background: Pertussis remains a significant cause of morbidity and mortality among young infants. Although tetanus and diphtheria have a low incidence, they remain important components of combined maternal vaccination strategies. Maternal immunisation with the tetanus, diphtheria and pertussis (Tdap) vaccine is recommended to protect newborns during early life. This study aimed to determine the prevalence and factors associated with Tdap vaccination acceptance among pregnant women at a university hospital. Methods: A cross-sectional study was conducted among 330 pregnant women at a university hospital in Selangor, Malaysia, using systematic random sampling based on inclusion and exclusion criteria. Data were collected using a validated, self-administered questionnaire. Logistic regression analysis was performed to identify factors associated with Tdap vaccination acceptance. Results: The overall response rate was 91.8% and the prevalence of Tdap vaccination acceptance was 76.6%. Significant predictors of Tdap vaccination acceptance were a history of vaccination (AOR = 5.744, 95% CI:1.869–17.654, p = 0.002), a positive attitude towards Tdap vaccination (AOR = 1.344, 95% CI:1.139–1.586, p = 0.002), the availability of Tdap vaccine at the healthcare facility (AOR = 50.810, 95% CI:17.246-149.693, p < 0.001) and counselling and recommendation from healthcare providers (AOR = 16.840, 95% CI:1.768-160.395, p = 0.014). Conclusion: The findings highlight the importance of addressing both individual and healthcare service factors to enhance Tdap vaccination acceptance during pregnancy. To improve acceptance, it will be essential to promote routine adult vaccination, strengthen public health messaging through targeted health education, and implement attitude-focused interventions to address uncertainties. Simultaneously, it is important to ensure consistent vaccine availability and equip healthcare providers with adequate knowledge and effective communication skills.